1997
DOI: 10.1007/pl00002463
|View full text |Cite
|
Sign up to set email alerts
|

Aufwachverhalten und psychomimetische Reaktionen nach S-(+)-Ketamin

Abstract: Ketamine is a racemic mixture containing equal parts of S-(+)-ketamine and R-(-)-ketamine. Their potency relation is approximately 4:1. In early human studies S-(+)-ketamine was presumed to produce the desired anaesthetic effects and R-(-)-ketamine the undesired psychic emergence reactions. Therefore, ketamine was compared in a number of randomised studies in volunteers and patients with racemic ketamine. This review addresses the impact of S-(+)-ketamine on recovery from anaesthesia, incidence and content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 0 publications
0
12
0
4
Order By: Relevance
“…S-ketamine was developed to decrease psychotomimetic side-effects of racemic ketamine but a review suggests that this is not clearly the case [7]. Another side-effect of ketamine as well as S-ketamine is hypersecretion.…”
Section: Discussionmentioning
confidence: 99%
“…S-ketamine was developed to decrease psychotomimetic side-effects of racemic ketamine but a review suggests that this is not clearly the case [7]. Another side-effect of ketamine as well as S-ketamine is hypersecretion.…”
Section: Discussionmentioning
confidence: 99%
“…If required, an additional bolus of methohexital was given before transfer to the scanner room. Group 2 received the sedation protocol consisting of a rectal bolus of 0.5 mg·kg −1 midazolam and 5 mg·kg −1 S‐(+)‐ketamine [equipotent to 10 mg·kg −1 racemic ketamine ( 6)], insertion of an intravenous cannula and two nasal prongs for additional oxygen supply (2–3 l·min −1 ) and sample aspiration for continuous monitoring of the nasopharyngeal endtidal pCO 2 signal. Additional intravenous boluses of 0.05 mg·kg −1 midazolam and 0.25 mg·kg −1 S‐(+)‐ketamine were administered until adequate immobilization for scanning was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…In 1997, one of the two optical enantiomers contained in the racemic mixture ketamine became available in purified form. Several studies revealed clinical superiority of S‐(+)‐ketamine compared to its optical enantiomer R‐(−)‐ketamine concerning anaesthetic potency ( 5), recovery time ( 6) and neuroprotective effects ( 7). Thus, a sedation technique based on S‐(+)‐ketamine and midazolam might combine the well known advantages of ketamine [oral and rectal route of administration ( 8, 9), large margin of safety concerning cardiovascular and respiratory depression ( 10)] with a potential reduction in adverse effects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Eine verkürzte Aufwachphase im Vergleich zum bisher verfügbaren Razemat wird auch dem S-(+)-Ketamin zugesprochen, neben einer möglicherweise geringeren Ausprägung der psychischen Aufwachreaktion [15,25]. Diese Eigenschaften und die höhere analgetische und anästhetische Potenz des S-(+)-Enantiomers erneuern das intensivmedizinische Interesse an diesem Analgosedativum, wobei gerade im intensivmedizinischen Bereich eine Halbierung der erforderlichen Substanzmenge einen wichtigen pharmakokinetischen Fortschritt darstellt.…”
Section: Die 90er Jahreunclassified